2006
DOI: 10.1111/j.1540-8183.2006.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

A 5Fr Catheter Approach Reduces Patient Discomfort during Transradial Coronary Intervention Compared with a 6Fr Approach: A Prospective Randomized Study

Abstract: Smaller guiding catheters can help reduce local complications and patient morbidity during transradial coronary intervention (TRI). This study was designed to compare the patient's morbidity, success rate, and the operator's convenience between 5-French (5Fr) and 6-French (6Fr) TRIs. This is a single-center prospective randomized study. Patients who underwent TRI, in 2003, were prospectively randomized to either 5Fr or 6Fr catheter groups (100 patients in each group). Procedure-related patient morbidity as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 9 publications
2
45
0
1
Order By: Relevance
“…As the whole procedure was finished inside the sheath and did not stimulate the radial artery directly, the approach was convenient for extending the catheters to the left ventricle for mapping the mitral annulus and for determining the ablation sites, without incurring radial artery spasm in any patient, indicating this method is a safe alternative approach for ablation. As Gwon et al pointed out, 20 PCI via the radial artery using a 5Fr catheter can reduce patient discomfort during the procedure because of the smaller diameter of the catheter, and the results of the present study also support this advantage in RFCA.…”
Section: Safetysupporting
confidence: 86%
“…As the whole procedure was finished inside the sheath and did not stimulate the radial artery directly, the approach was convenient for extending the catheters to the left ventricle for mapping the mitral annulus and for determining the ablation sites, without incurring radial artery spasm in any patient, indicating this method is a safe alternative approach for ablation. As Gwon et al pointed out, 20 PCI via the radial artery using a 5Fr catheter can reduce patient discomfort during the procedure because of the smaller diameter of the catheter, and the results of the present study also support this advantage in RFCA.…”
Section: Safetysupporting
confidence: 86%
“…10,19 In addition, compliance and the ability of the radial artery to distend are reduced in patients with risk factors such as atherosclerosis, and endothelial dysfunction of radial artery is believed to correspond with the severity of CAD. 20,21 Nevertheless, a recent Korean study reported that the mean diameter of the radial artery was 2.60± 0.41 mm and one Japanese study further revealed that the reduction of radial artery flow after transradial PCI was less likely if the ratio of radial artery diameter to sheath outer diameter was ≥1.0.…”
Section: Discussionmentioning
confidence: 99%
“…12,38 It is interesting to note that an S-A ratio Ͼ1 is associated with pain during sheath insertion and removal. 41 In a prospective, randomized trial designed to test the hypothesis that sheath-artery mismatch contributes to RAO, Dahm et al 42 assigned patients to receive transradial PCI by means of a 5F system or a 6F system. Procedural success was similar between the 2 groups, but there was less RAO in the 5F group (1.1% versus 5.9%, Pϭ0.05).…”
Section: Sheath Sizementioning
confidence: 99%
“…38,40,41 Associations between radial artery diameter and body height, body weight, and body surface area are weak (rϭ0.23-0.33). 38,40,41 Brachial artery diameter may correlate more closely with body size, whereas the relative size of the radial and ulnar arteries is less predictable. The radial artery is larger than the ulnar in 51% of patients.…”
Section: Sheath Sizementioning
confidence: 99%